PENGARUH PELATIHAN KARYAWAN, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI BLUE SKY PANDURATA BOUTIQUE HOTEL JAKARTA - Noviana Ayuningtias; Bonifasius M.H Nainggolan (Human Capital Development, 2019)
Purpose- This study aimed to analyze the effect of employee training, work discipline and motivation on employee performance either partially or simultaneously at Blue Sky Pandurata Boutique Hotel Jakarta. Design/methology/approach- In this research the sample used is employees of Blue Sky Pandurata Boutique Hotel consisting of 62 respondents, purposively due to time and cost limitation. Analytical technique using multiple linear regression including its classic assumption test. Hyphotheses testing by F, t test, coorelation and determination test . Findings- In this research the sample used is employees of Blue Sky Pandurata Boutique Hotel consisting of 62 respondents. Analytical technique using multiple linear regression. It was found that training had a positive and significant influence on the performance of employees of Blue Sky Pandurata Boutique Hotel Jakarta at 7.56%; Discipline has a positive and significant influence on employee performance at Blue Sky Pandurata Boutique Hotel Jakarta of 10.69% and the motivation variable has a positive and significant influence on employee performance of Blue Sky Pandurata Boutique Hotel Jakarta at 8.58%. The conclusion of training, discipline, and motivation simultaneously have significant influence on employee performance at Blue Sky Pandurata Boutique Hotel Jakarta that is equal to 63,04%, the rest equal to 36,96% influenced by other factors not discussed in this research, such as competence, compensation , leadership, appreciation, organizational culture and other things.